Mutations in CRLF1 cause familial achalasia. Issue 1 (15th March 2017) - Busch, A.; Žarković, M.; Lowe, C.; Jankofsky, M.; Ganschow, R.; Buers, I.; Kurth, I.; Reutter, H.; Rutsch, F.; Hübner, C.A.
Abstract : We here report a family from Libya with three siblings suffering from early onset achalasia born to healthy parents. We analyzed roughly 5000 disease‐associated genes by a next‐generation sequencing (NGS) approach. In the analyzed sibling we identified two heterozygous variants in CRLF1 (cytokine receptor‐like factor 1). Mutations in CRLF1 have been associated with autosomal recessive Crisponi or cold‐induced sweating syndrome type 1 (CS/CISS1), which among other symptoms also manifests with early onset feeding difficulties. Segregation analysis revealed compound heterozygosity for all affected siblings, while the unaffected mother carried the c.713dupC (p.Pro239Alafs*91) and the unaffected father carried the c.178T>A (p.Cys60Ser) variant. The c.713dupC variant has already been reported in affected CS/CISS1 patients, the pathogenicity of the c.178T>A variant was unclear. As reported previously for pathogenic CRLF1 variants, cytokine receptor‐like factor 1 protein secretion from cells transfected with the c.178T>A variant was severely impaired. From these results we conclude that one should consider a CRLF1 ‐related disorder in early onset achalasia even if other CS/CISS1 related symptoms are missing. Abstract :